Slum area family communication in shapeing children’s personality during the Covid-19 pandemic - sigit hardiyanto, Sigit Hardiyanto; Muhammad, Daffa; qarin ensri hidayat, Qarin Ensri Hidayat (COMMICAST, 2022)
Frightening specter for families because this virus can cause death if it does not limit social interaction in carrying out various daily activities. This virus was first reported in Wuhan, Hubei Province, China. The impact of this virus does not only attack and kill human organs. Among the city's residents, the covid-19 crisis has had a disproportionate impact on residents in slum areas (slum areas), especially in the city of Medan. The problem that is said to be a crisis can befall a family is when individuals in the family there is a clash of values between family members, especially between parents and children who have different views between generations. This research is a type of qualitative research with a focus of study, especially on how family communication in the slum area of Medan City forms the personality of children during the covid-19 pandemic. The informants in this study were parents who had children at the age of 6-12 years old. Data collection techniques in this study used structured interviews, and documentation. The results of this study can be seen in shaping the child's personality to overcome all actions that violate the rules, then there are several communications built by the slum area family in shaping the development of the child's personality, including messages of advice that are always carried out by parents. Parents in general have an interest in their children by giving attention in the form of advice to their children regarding activities carried out by children in general so that messages conveyed through communication can run well. The advice given by parents usually makes a comparison picture of the good or bad of an activity carried out by the child so that the child can determine the attitude of the advice given by his parents.